CRITICAL ANALYSIS ON THE IMPACT OF LABORATORY TESTING ON EMERGENCY MEDICINE IN ENHANCING LABORATORY AND PHARMACY COLLABORATION TO REDUCE MEDICATION ERRORS. - 1Abdullah Saad M Lsallum, 2Hamdan Hussain D ALsallum, 3Shakhis Daws D Alsallum, 4Salem Hussain M Alsallum, 5Abdullah Khalid A Humayyim, 6Mohammed Hussain M ALsallum, 7Ali Mohammed A Alsallum, 8Hussain Mesfer Hamad, 9Abdullah mohammed S Alsallum,,; 10Hassan Muidh H Lasslom, 11Ali Oshima H Alsalia, 12Abdulla Hamad A Almuhtariq, 13AbdulRahman Bashir M AlBalawi, 14Hassan hebah thabet Hassan, 15Mohammed Saidan S Almakhlas, (Chelonian Research Foundation, 2022)
In emergency medicine, laboratory testing is pivotal for timely diagnosis and treatment. Nonetheless, medication errors pose a substantial risk. This article analyzes the effect of medication testing on emergency medicine, highlighting expanded collaboration between research facilities and pharmacy to address medication mishandling. Through a comprehensive writing audit and subjective examination, essential techniques to make strides in collaboration and diminish mistakes are recognized. The discoveries highlight the significance of collaboration, innovation, and quality change measures. Proposals are advertised to make strides in the coordination of clinical trials and emergency therapeutic administrations and guarantee patient safety and progress outcomes. Keywords: laboratory testing, emergency medicine, pharmacy, collaboration, medication errors